Manajemen Pembelajaran PAI Untuk Penguatan Karakter Religius Peserta Didik Pondok Pesantren Al-Kautsar Tebo Tengah - Sumirah Sumirah; Siti Sakinah; Atika Dhanasari (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the management of Islamic Religious Education (PAI) learning in developing students’ religious character at Pondok Pesantren Al-Kautsar Tebo Tengah. Employing a qualitative case study design, data were collected through observations, in-depth interviews, and documentation. The results demonstrate that value-oriented learning management, combined with daily religious routines and structured parental involvement, effectively strengthens the internalization of Islamic values. Teachers function not only as instructors but also as role models who facilitate meaningful religious experiences. The findings further reveal that the implementation of Higher Order Thinking Skills (HOTS)-based learning strategies enhances students’ ability to understand and apply Islamic values reflectively. The novelty of this study lies in its integrated model that connects learning management, religious habituation, and parental engagement within a pesantren-based elementary school context. Theoretically, this research contributes to the development of a holistic framework for PAI learning management, while practically it provides a collaborative school–parent model applicable for strengthening students’ religious character